Treatment with tucumã oil (Astrocaryum vulgare) for diabetic mice prevents changes in seric enzymes of the purinergic system: Improvement of immune system - Baldissera M.D. (2017)
© 2017 Elsevier Masson SASThe aim of this study was to evaluate the enzymatic activity of the purinergic system in sera samples from alloxan-induced diabetic mice treated with tucumã oil (Astrocaryum vulgare). For this, the mice were divided into four groups (n = 6): control/water (the group CW); control/tucumã oil (the group CT); diabetic/water (the group DW), and diabetic/tucumã oil (the group DT) treated for 14 days with 5.0 mL kg−1 via oral gavage. On day 14 post-treatment, mice were submitted to euthanasia and blood samples were collected by cardiac puncture. Tucumã oil treatment significantly decreased (p < 0.05) blood glucose levels in the group DT compared to the group DW. These results demonstrated an increase (p < 0.05) in NTPDase (adenosine triphosphate (ATP substrate) or adenosine diphosphate (ADP substrate)), 5′-nucleotidase (AMP substrate) and adenosine deaminase (ADA; adenosine substrate) activities in serum from the group DW compared to the group CW. Tucumã oil treatment prevented these alterations in the group DT compared to the group DW, and restored these parameters near to the group CW. In summary, the treatment with tucumã oil was able to modulate the alterations caused by hyperglycemia probably by the presence of carotenoids compounds, maintaining normal levels of ATP, ADP, AMP and adenosine, molecules that could exhibit anti-inflammatory properties, depending on their concentration. Thus, the tucumã oil is a promising natural compound with protective action against diabetes and its side effects, such as changes in the purinergic system, improving the immune system.